2023
DOI: 10.1128/aac.01419-22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of a Novel Antifungal, Fosmanogepix, in Patients with Candidemia Caused by Candida auris : Results from a Phase 2 Trial

Abstract: Fosmanogepix (FMGX), a novel antifungal available in intravenous (IV) and oral formulations, has broad-spectrum activity against pathogenic yeasts and molds, including fungi resistant to standard of care antifungals. This multicenter, open-label, single-arm study evaluated FMGX safety and efficacy for treatment of candidemia and/or invasive candidiasis caused by Candida auris .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 36 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…FMGX was rapidly converted to MGX after IV administration (Table S2), similar to observations from previous PK evaluations of FMGX with measurable FMGX concentrations available for only 4–24 h after IV infusions on days 1–7 ( 12 ). Geometric mean plasma concentrations of MGX on day 1 were highest for cohort A, with a loading regimen of 1,500 mg/3 h BID (9 h apart).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…FMGX was rapidly converted to MGX after IV administration (Table S2), similar to observations from previous PK evaluations of FMGX with measurable FMGX concentrations available for only 4–24 h after IV infusions on days 1–7 ( 12 ). Geometric mean plasma concentrations of MGX on day 1 were highest for cohort A, with a loading regimen of 1,500 mg/3 h BID (9 h apart).…”
Section: Resultssupporting
confidence: 85%
“…One event each of AST and ALT elevation occurred while participants were taking FMGX at home; neither was considered to be clinically significant. These findings support the duration and provide a detailed PK profile of the treatment regimen assessed in the phase 2 efficacy and safety studies of FMGX for the treatment of candidemia and/or invasive candidiasis caused by Candida auris (NCT04148287) ( 12 ) and invasive aspergillosis and other rare molds (NCT04240886) ( 6 , 13 , 14 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The first (NCT03604705; clinicaltrials.gov ) was an open-label, non-comparative study assessing the safety and efficacy of fosmanogepix in the treatment of non-neutropenic patients with candidemia which met its primary efficacy endpoint with a treatment success rate of 80% with an acceptable safety profile ( 54 ). The second study (NCT04148287; clinicaltrials.gov ) tested the safety and efficacy of fosmanogepix treatment in patients with candidemia caused by C. auris ( 55 ). Treatment success at the end of study treatment and day 30 survival were 89% with no treatment-related adverse events or study drug discontinuations reported.…”
Section: Discussionmentioning
confidence: 99%
“…Initial results from completed Phase 1 and 2 clinical trials are in line with published preclinical and in vitro susceptibility data and animal models of infection. 18–21 The overall goals for the clinical development programme are to determine if fosmanogepix is a safe and effective treatment option for IFDs caused by the major pathogenic fungi (i.e. Candida , Cryptococcus and Aspergillus spp.)…”
Section: Introductionmentioning
confidence: 99%